A compreensão do sujeito bolsista em relação ao programa universidade para todos: Prouni, à luz do pensamento complexo - Ferreira, José Angelo (2012)
The PROUNI came up with the interim measure no. 213 of 09/10/2004, subsequently enacted into law under the paragraph. 11.096 de 01/13/2005, which regulates the offers of scholarships and partial integrals in Higher Education Institutions (ISEs), through tax breaks in return for the supply of these jobs, seeking to soften the gap between students of low income graduates of public schools, particularly blacks and Indians. The objective of this study is to understand the subjective dimensions of scholarship students from the University for All Program - PROUNI, London School of Pythagoras, to the Program in its multiple dimensions. The research part of the questioning of what is the understanding of the subject in relation to the PROUNI in its dimension of social inclusion, cultural and economic. The approach of this research is qualitative, depending on the nature of the problem, which requires an understanding of a situation in depth, with emphasis on the meaning given by the stakeholders and participants in this research are PROUNI Fellows Program for undergraduate courses in Business Administration, Communication, Law, Nursing, Engineering, Education and Psychology. We interviewed 30 subjects, randomly selected among students participating in the Program. This research turns to the analysis of statements by the subjects investigated, thus allowing to understand the subjective perceptions of student scholarships. The theoretical framework underlying the research is complex thinking, whose lead author is Edgar Morin in his conception of the subject. To achieve this purpose, it was first to study the emergence of PROUNI within a historical context, political and economic development, highlighting the historical and political role played by social movements for the realization of the University Program for All as an inclusive public policy in then spoke up on the notion of the subject, starting with the Cartesian subject and concluding with the notion of subject in the light of complex thinking, followed by field research in which they sought in the speeches of fellow students, their understanding about their own Program. It was during the research that the subject PROUNI scholarship from the Faculdade Pitágoras de Londrina, has understanding of the program on multiple dimensions such as social inclusion, cultural and economic.